2018
DOI: 10.1038/s41538-018-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary compounds have potential in controlling atherosclerosis by modulating macrophage cholesterol metabolism and inflammation via miRNA

Abstract: Atherosclerosis (AS) is a typical example of a widespread fatal cardiovascular disease. Accumulation of cholesterol-laden macrophages in the artery wall forms the starting point of AS. Increased influx of oxidized low-density lipoprotein to macrophages and decreased efflux of free cholesterol out of macrophages constitute major factors promoting the development of AS. Inflammation further aggravates the development of AS along or via interaction with the cholesterol metabolism. Many microRNAs (miRNAs) are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 113 publications
2
21
0
1
Order By: Relevance
“…Our previously published studies have already shown that AAE reduces total cholesterol levels both in vitro, in hepatic cultured cells, as well as in vivo, in humans affected by mild hypercholesterolemia [29,42]. Our results confirm those published by other groups and presenting similar effects exerted by other polyphenolic extracts [16,17,43,44,45,46,47]. However, whether the cholesterol lowering effect of AAE is due to i) reduced cholesterogenesis, ii) increased cholesterol excretion or iii) increased conversion of cholesterol into bile acids remains elusive.…”
Section: Resultssupporting
confidence: 91%
“…Our previously published studies have already shown that AAE reduces total cholesterol levels both in vitro, in hepatic cultured cells, as well as in vivo, in humans affected by mild hypercholesterolemia [29,42]. Our results confirm those published by other groups and presenting similar effects exerted by other polyphenolic extracts [16,17,43,44,45,46,47]. However, whether the cholesterol lowering effect of AAE is due to i) reduced cholesterogenesis, ii) increased cholesterol excretion or iii) increased conversion of cholesterol into bile acids remains elusive.…”
Section: Resultssupporting
confidence: 91%
“…Ox-LDL exhibits strong affinity for scavenger receptors found on mononuclear macrophages, leading to its quick internalisation ( 21 ). However, Ox-LDL is toxic for macrophages, causing them to become activated, rapidly proliferate, aggregate and degenerate ( 22 ). Finally, the macrophages undergo apoptosis and become foam cells, which then aggregate to form AS lipid plaques.…”
Section: Factors Implicated In Asmentioning
confidence: 99%
“…In addition, many plant-derived compounds were recently suggested to exert their anti-inflammatory effect through regulating the expression of proinflammatory miRNAs, especially those upregulated after NF-kB activation (120). Although a few reports indicate the precise mechanisms that regulate or deregulate the expression of miRNAs, growing evidence suggests that phytochemicals regulate the expression of miRNAs by interfering with the processes associated with the miRNAs processing and maturation, and these phytochemicalmediated alterations in miRNAs biosynthesis machinery could in part contribute to the miRNAs dysregulation by either increasing or decreasing their levels (121,122).…”
Section: Plant-derived Compounds Modulating the Tlr4/nf-kb Pathway Anmentioning
confidence: 99%